IMPROVING TABLE TEXT COMPREHENSION THROUGH CONTEXTUAL LEARNING IN ENGLISH SUBJECT FOR GRADE VIIC STUDENTS AT SMPN 2 SOA - Meo, Florianus Kugu (Jurnal Analisis Pendidikan Sosial, 2025)
Understanding table texts in English is a challenge for junior high school students due to the lack of effective learning strategies. Initial observations at SMPN 2 Soa revealed that seventh-grade students struggled to identify information, understand data relationships, and draw conclusions from tables. Contextual Teaching and Learning (CTL) was chosen to connect the material with students' real-life experiences to enhance their comprehension. This study aims to describe the implementation of CTL, measure its effectiveness in improving table text comprehension, and identify challenges faced by students. This Classroom Action Research (CAR) was conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. The subjects were Grade VIIC students at SMPN 2 Soa. Data were collected through tests, observations, and interviews, and analyzed using descriptive statistics. Results from Cycle 1 showed an increase in the average score from 51.1 to 65.6, but only 17.24% of students met the target (?70). In Cycle 2, a more interactive strategy was applied, raising the average score to 78.6, with 90 % of students achieving the target, demonstrating the effectiveness of CTL.